Study of the environmental pollutants of petroleum nature from spent refining water in Beiji refinery - Abid A. Erdini (Tikrit Journal of Pure Science)
In this research work, separation and identification of some petroleum components in wastewater in Beiji. The petroleum components and hydrocarbons were extracted from the wastewater by CCl4. The extract after evaporation of the solvent was fractionated using liquid-liquid extraction employing ethyl methyl ketone to remove paraffinic waxes-residual materials were redissolved in CCl4 to remove any contamination. The residue remained after the removal of the solvent was transferred quantitatively to prepacked silica gel column (100-120) mesh which was activated at 300 °C. Silica gel column was washed by using the following solvent: hexan, toluene, chloroform and ethanol. It was found apparent that the separated component were of paraffinic, aromatic and heterogenous, nature for the solvent mentioned above, respectively. The confirmation of such nature was performed by using infrared spectrophotometer technique